The Effectiveness of the Flipped Classroom Method on Students’ Speaking Ability: A Meta-Analysis Study - Senjaya, Elisabet Ani Ayu; Ali Muhtadi (JTP - Jurnal Teknologi Pendidikan, 2023)
Many studies have investigated the effectiveness of the flipped classroom method on students’ speaking ability when compared to traditional learning methods. However, previous research has provided ambiguous results. This study aims to test the effectiveness of the flipped classroom method on students’ speaking abilities compared to traditional methods, as well as investigate what factors can influence the effectiveness of using the flipped classroom method on students’ speaking abilities. The design used in this study was group contrast meta-analysis by analyzing 15 primary studies that met the inclusion criteria. The results of the analysis using the random-effects approach obtained a combined effect size of (g = 1.25; p < 0.01). The effect size is in the "Large Effect" category. It can be concluded that the use of the flipped classroom method on students’ speaking ability has a significant and more effective effect compared to traditional learning methods. Heterogeneity analysis found that the moderator variable educational level influenced the effectiveness of implementing the flipped classroom method on students’ speaking abilities, but not the moderator variables educational level, experimental class capacity, and region. The findings of this meta-analysis provide more accurate results regarding inconsistent effect size variations and can enrich insight into knowledge about the effectiveness of using the flipped classroom method in improving students’ speaking skills.